Biopsy‐free screening for glioma - Cheng, Alexandre Pellan (EMBO Mol Med, 2018)
Circulating tumor DNA (ctDNA) is a promising diagnostic marker for many cancers and can be noninvasively assayed from blood. For diagnosing glioma, this approach has unfortunately proven to be of limited use since glioma contribute minimal ctDNA to the blood circulation. A more promising avenue may therefore be to hunt for ctDNA in cerebrospinal fluid (CSF). The study by Mouliere et al in this issue of EMBO Molecular Medicine demonstrates that shallow whole‐genome sequencing of CSF‐cfDNA can be used to detect copy number alterations in glioma‐derived ctDNA, providing a low cost strategy to screen for glioma.